Pengaruh Penggunaan Alat Peraga Timbangan Bilangan Terhadap Pemahaman Konsep Perkalian di Kelas II SD Islam Al Azhar 15 Pamulang - Fery Muhamad Firdaus; Ririn Novita Sari (Program Studi PGSD, Fakultas Ilmu Pendidikan, Universitas Negeri Yogyakarta, 2019)
This study aims to know the use of numerical weighing tools against the suspension of mathematics concepts of students of class II Islamic El Al Azhar 15 Pamulang on multiplication materials. The numerical weighing tool is a semi-concrete tool or a machine that is working on an operation task. This research was conducted in the second grade of Al Azhar Islamic Elementary School 15 Pamulang. The method used in this research is quasi experimental method with The Nonequivalent Posttest-Only Control Group Design research design. The sample in this study consisted of an experimental class using 26 students and a control class directed by 26 students. Instrumen is used in this reseach such us mathematical conceptual ability written essay test. The results showed that the students used by using the instrument of numerical scales using the average ability to comprehend the concept of mathematics students is higher than the average ability to understand the concept of mathematics students who are taught without using the means of weighing the scale of the value of significance 0,001 0.05. Based on result of effect (effect size) obtained d value equal to 0,819. The value of the effect of the size obtained interprets that the use of numerical weights of numerals has a high category. Thus, this shows that there is an influence of the use of numerical weighing tools on the ability to understand the concept of mathematics students in class II Islamic Elementary School Al Azhar 15 Pamulang.